Accelerating Effects of Poloxamer and Its Structural Analogs on the Crystallization of Nitrendipine Polymorphs - Jie Zhang; Qiusheng Yang; Meixia Xu; Xinqiang Tan; Xucong Peng; Ziqing Yang; Kang Li; Jia Yang; Jie Chen; Xuan Xun; Saijun Xiao; Lingjie Zhou; et al. (Pharmaceuticals)
Background: Surfactants can be added into polymer–amorphous drug systems to further enhance solubility. However, this may cause amorphous drugs to become physically unstable, and the inherent mechanism at play here is not fully understood. Methods: We explored the effects of poloxamer, a poly (ethylene oxide)-poly (propylene oxide)-poly (ethylene oxide) (PEO-PPO-PEO) triblock copolymer surfactant, and its segments on the nucleation and growth kinetics of amorphous nitrendipine (NTP) from the melt through polarized light microscopy. The effects of poloxamer and structural analogs on the melting point and glass transition temperature were also investigated using differential scanning calorimetry. Results: The poloxamer and its structural analogs enhanced nucleation and growth kinetics in supercooled liquid. Poloxamer and its structural analogs exhibited similar effects on the nucleation and growth kinetics of amorphous NTP, suggesting minimal dependence on structural variation. The overall crystallization rate of the NTP increased when increasing the poloxamer content and ultimately reached a maximum value; after that, the crystallization rates of NTP decreased when increasing the poloxamer content. Conclusions: Poloxamer and its structural analogs achieve similar effects on crystallization due to their comparable plasticizing effects. The nucleation and growth rates show different trends as a function of the poloxamer content. This effect is a result of both kinetic and thermodynamic factors. This study is relevant to understanding the impacts of the surfactant on the physical instability of amorphous drugs.